PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 31 PADANG - Prima Ryan Perdana (Jurnal Edukasi dan Penelitian Matematika, 2019)
Understanding the concept of mathematics is a cognitive ability that every learner is expected to have in mathematics learning. However, in fact, the learners ' learning outcomes are seen that understanding the mathematical concepts is still low, so it needs to be improved. The solution to overcome this is to implement a learning approach so as to facilitate the understanding of the material and build its own knowledge of the Contextual Teaching and Learning (CTL) cooperative model for The equation and linear inequalities of one variable are easy to understand. This type of research is pre-experimental research with The One-Shot Case Study Draft and focused on the assessment of final test results understanding The mathematical concept of learners. Based on the analysis of the test results understanding of the mathematical concepts given is derived that the indicators classify the objects based on the presence of the requirements in forming concepts, giving examples and examples of cons of a concept, and Presenting concepts in various mathematical representations more effectively than the indicators of understanding the other concepts. This indicates that the application of the CTL-type cooperative learning model can describe the understanding skills of the student concept.Key Words – Contextual Teaching and Learning approach, Mathematical Concepts Understanding Key Words – Contextual Teaching and Learning approach, Mathematical Concepts Understanding